Peran Literasi Digital dan E- Commerce Terhadap Keputusan Pembelian Online - Kisthi Hanila Dewi (Coopetition : Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the role of digital literacy and e-commerce on online purchasing decisions. The method used in this study is a quantitative research method with research samples using online platforms and using a scale of digital literacy, e-commerce, and online purchasing decisions as well as a purposive sampling technique. The results of the research based on the results of statistical analysis of the coefficient of determination or (R square) have a value of 0.487 or 48.7%, this number means that the influence between digital literacy and e-commerce on online purchasing decisions is moderate. So by increasing high digital literacy it will enable individuals to more easily find, evaluate, and buy products or services through e-commerce.